2018
DOI: 10.1177/1468794118777921
|View full text |Cite
|
Sign up to set email alerts
|

Feeling ‘like a minority . . . a pathology’: interpreting race from research with African and Caribbean women on violence and abuse

Abstract: Qualitative researchers are often advised to use their emotional responses to data, and participants' experiences are understood through those of researchers', how this process unfolds is less clear. This paper is about role of feelings for the qualitative researcher at different stages of the process and offers strategies for working through, 'using' and 'feeling together with' participants, reflections on lived experiences. I interviewed nine African and Caribbean heritage British women about their experienc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…The ability of a blogging site to be used for comments, both by potential participants and by those seeking to disrupt the research, was not considered at this point. The link to the research site was shared across several well-known feminist blogging sites and online platforms targeting specific communities that have been considered 'hard to reach' for sexual violence research due to low rates of disclosure and barriers to help-seeking (Washington, 2001;Kanyeredzi, 2013), including black women forums and specialist sexual violence services. Over one-hundred requests for participation were received within a twenty-four-hour period, significantly exceeding initial expectations of the levels of participation.…”
Section: Research Interruptedmentioning
confidence: 99%
“…The ability of a blogging site to be used for comments, both by potential participants and by those seeking to disrupt the research, was not considered at this point. The link to the research site was shared across several well-known feminist blogging sites and online platforms targeting specific communities that have been considered 'hard to reach' for sexual violence research due to low rates of disclosure and barriers to help-seeking (Washington, 2001;Kanyeredzi, 2013), including black women forums and specialist sexual violence services. Over one-hundred requests for participation were received within a twenty-four-hour period, significantly exceeding initial expectations of the levels of participation.…”
Section: Research Interruptedmentioning
confidence: 99%
“…One school explained that they had already had several researchers working at the school and could not accommodate any more. This decision alluded to the historical reluctance marginalised groups, particularly black communities, have expressed towards research, given its use to reinforce harmful stereotypes (Daniel, 2005;Kanyeredzi, 2018). The school's rejection of my research and the wider failure of this initial recruitment strategy demonstrated the limitations of a social justice-oriented research methodology if it could not be effectively or persuasively communicated to potential participants.…”
Section: Negotiating Sameness and Blacknessmentioning
confidence: 99%
“…Eleanor was not the only interviewee to express belief in the power of a particularly black re-appropriation of attachment parenting and indeed, approval of how my research project might work to promote AP in black communities. The interviewees' articulation of attachment parenting as a protective mechanism for the black community meant that my responsibility to portray them respectfully, explicitly rejecting exploitative stereotypes that have emerged from historic research on black folk (Daniel, 2005;Kanyeredzi, 2018), might be mistaken for a duty to describe attachment parenting favourably. The women's hopes that my project might popularise attachment parenting among mothers was evidently a motivation for participation in the project.…”
Section: Negotiating Sameness and Blacknessmentioning
confidence: 99%
“…Indeed, stories of suffering and distress played an important role in my early analysis as I processed vicarious trauma from the field. Fieldwork trauma is a documented experience among researchers including research students (Pollard 2009;Clark 2017;Kanyeredzi 2018). Both Janine Natalya Clark (2017) and Ava Kanyeredzi (2018) discuss struggling with the data analysis following traumatic fieldwork, and making sense of emotion in data.…”
Section: Approach To Data Analysismentioning
confidence: 99%
“…Fieldwork trauma is a documented experience among researchers including research students (Pollard 2009;Clark 2017;Kanyeredzi 2018). Both Janine Natalya Clark (2017) and Ava Kanyeredzi (2018) discuss struggling with the data analysis following traumatic fieldwork, and making sense of emotion in data. While working through data transcription and analysis, I sought external supervision to assist with these experiences and took an extended break of several months.…”
Section: Approach To Data Analysismentioning
confidence: 99%